Seasonal variation of some physico-chemical parameters from Erai river water at three different stations near Chandrapur district (M.S.) India (International Journal of Food and Nutritional Sciences, 2023)
To assess the water quality of Erai river were investigated on monthly basis for a period of two year by using standard procedures at three different sampling stations, seasonal variations in water temperature, pH, total alkalinity, total hardness, calcium and magnesium were recorded. The nutrients are included in sufficient amount for the growth of aquatic organisms in the river. Present work also embodies suggestion for the conservation of river environment.